Study Constraints And Troubleshooting Affective Learning in Islamic Education At High School In Yogyakarta (STAI Miftahul Ula Nganjuk, 2016)
This article is about a descriptive-qualitative research made to identify and describe the constraints of affective learning in the religious education affiliated to Islam at senior high schools in the city of Yogyakarta and the alternative strategies of problem: solving used by teachers of the religion in Overcoming the constraints. The research of data were collected from the whole population of such teachers at both state and private senior high schools all over the city by using questionnaires and interview guidelines. The research findings indicate that, in conducting affective teaching, Reviews those teachers are faced with numerous constraints related to Reviews their students self-esteem, interest, motivation, attitude, value system, and faith. The constraints may be internal or external in origin, that is, the caused by factors coming from the students Themselves or by Reviews those coming from elsewhere. The teachers Efforts to Overcome the constraints may Also be internal in type, made to solve problems the caused by factors of the first type above, or external in type, made to solve: problems the caused by factors of the second type above the which have a share in causing the constraints of external in origin. In addition, the findings Also indicate that, in general, the teachers still lack _full understanding of and are not yet fully aware of the models of affective teaching they use. Also They are still highly lacking in understanding the six types of constraints. Consequently, in coping with and taking an attitude towards the constraints, They also exhibit Differing reactions and Efforts in solving the problems.